2013
DOI: 10.1186/1471-2393-13-77
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of routine or case-based inquiry for intimate partner violence: a mixed method study

Abstract: BackgroundThe prevalence and detrimental health effects of intimate partner violence have resulted in international discussions and recommendations that health care professionals should screen women for intimate partner violence during general and antenatal health care visits. Due to the lack of discussion on routine or case-based inquiry for intimate partner violence during antenatal care in Germany, this study seeks to explore its acceptability among pregnant German women.MethodsA mixed methods approach was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
5
16
0
1
Order By: Relevance
“…In agreement with previous studies, competing demands, time constraints and lack of sufficient resources were mentioned as the hindering factors for delivering DFV interventions in healthcare settings [28,29]. System level changes such as training of HCPs, staff commitment, institutional support, onsite support services and effective collaboration with local stakeholders involved in providing support services are important for delivering continual and effective service to victims of DFV [40,43,44]. Considering the social stigma related to seeking help from DFV services and minimal funding in this area [8,10], integrating DFV program into routine ANC and/or PMTCT counselling services can be a potential cost-effective strategy to improve response mechanisms against DFV in resource-constrained settings like Nepal.…”
Section: Discussionsupporting
confidence: 77%
“…In agreement with previous studies, competing demands, time constraints and lack of sufficient resources were mentioned as the hindering factors for delivering DFV interventions in healthcare settings [28,29]. System level changes such as training of HCPs, staff commitment, institutional support, onsite support services and effective collaboration with local stakeholders involved in providing support services are important for delivering continual and effective service to victims of DFV [40,43,44]. Considering the social stigma related to seeking help from DFV services and minimal funding in this area [8,10], integrating DFV program into routine ANC and/or PMTCT counselling services can be a potential cost-effective strategy to improve response mechanisms against DFV in resource-constrained settings like Nepal.…”
Section: Discussionsupporting
confidence: 77%
“…This aligns with research from resource-rich settings suggesting that many pregnant and postpartum women are supportive of health providers inquiring about IPV (Eisenman et al, 2009;Ramsay, Richardson, Carter, Davidson, & Feder, 2002;Stöckl et al, 2013;Waalen, Goodwin, Spitz, Petersen, & Saltzman, 2000). This aligns with research from resource-rich settings suggesting that many pregnant and postpartum women are supportive of health providers inquiring about IPV (Eisenman et al, 2009;Ramsay, Richardson, Carter, Davidson, & Feder, 2002;Stöckl et al, 2013;Waalen, Goodwin, Spitz, Petersen, & Saltzman, 2000).…”
Section: Discussionsupporting
confidence: 70%
“…A survey among German women showed high acceptance of inquiry for intimate partner violence during antenatal care: 56 % supported routine screening, whereas 36 % preferred casebased inquiry. This finding was reported to be in line with previous studies that found higher acceptance of violence screening during pregnancy than during general care (Stöckl et al 2013). An Australian study also showed high acceptance of routine assessment for alcohol and drug use amongst pregnant women; only 15 % of surveyed women were uncomfortable about being screened (Seib et al 2012).…”
Section: Discussionsupporting
confidence: 93%